Keanekaragaman Lichenes sebagai Indikator Kualitas Udara di Kawasan Hutan Dengan Tujuan Khusus (KHDTK) Pujon Kabupaten Malang - Ardiansyah, Ivan; Rahardjanto, Abdulkadir; Waluyo, Lud (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2024)
Air is important for human survival, but in modern times, air quality is increasingly decreasing due to air pollution. Air quality can be seen in several aspects, one of which is the biological aspect. Lichenes are a biological aspect that can be used as an indicator of air quality. Lichenes are sensitive to the natural conditions in which they live, if air pollution occurs in their habitat it will disrupt their growth process. The aim of this research is to determine the air quality in the Pujon Special Purpose Forest Area, Malang Regency, based on the results of the diversity of spesies and size of Lichenes found. This research uses a quantitative approach and an exploratory descriptive research type. The method used was purposive sampling using a 10Ã—20m belt transect placed at stations I, II, and III in the Pujon Special Purpose Forest Area. Data analysis techniques include abiotic factor analysis, analysis of the size of Lichenes as an indicator of air quality, Shannon-Weiner (H') diversity, and analysis of macroscopic characteristics. The results of this research found that 27 spesies of Lichenes had been identified from 15 different families. The highest diversity index value was at station II (2.62), followed by station I (2.52), and the lowest at station III (2.41). Based on the spesies diversity index value, Lichenes are included in medium diversity. The average size of Lichenes at stations I, II, and III indicates that the air quality in the Pujon Special Purpose Forest Area is of very good quality.